APLIKASI SEVEN TOOLS UNTUK PERBAIKAN MUTU BAKSO DI PT KEPURUN PAWANA INDONESIA, KLATEN, JAWA TENGAH - , NUR AVICENIA YUSTICIA S, Ibnu Wahid Fakhrudin Aziz, STP, MT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The meatballs that not fit into company standard is a problem in PT Kepurun Pawana Indonesia (KPI). Although, in the company structure there is Quality Control division, but the reality on the ground, the division function is not implemented. Consequently, needed solutions to improve product quality and minimize the unwanted production result. This study is expected to be an alternative solution to repair ing quality meatballs problems in PT KPI. This study was using seven tools and statistical quality control methods. Attributes Quality in this factory are meatballs is doesn't cut and doesnât uniform meatballs. Analysis of the quality attributes made with bar charts, pareto diagrams, and C-Chart. Quality variable that is processed in this study is the size of the meatballs diameter. Analysis of the variable quality of meatballs made with X-R Chart. Cause and effect diagram is used to analyze the root causes of problems and identify measures to improve the quality of meatballs in PT KPI. Results from this study is from 5578 items of meatballs, contained 75 items of meatballs is doesnât cut and 103 items of meatballs is doesnât uniform. After analysis with C-chart from largest defect, the result is all of meatballs defects are in control. The results from the analysis of variable quality with X-R control chart is from 180 item contained 133 item of meatballs under lower control limits and 47 items of meatballs above upper control limits. The cause of the size of the meatballs diameter are outside of the control limit is the size of the knife in the meatball molding machine suddenly changed and the volume of dough is unstable. Both factors caused because PT KPI doesnât have ideal management and quality control system for an agricultural industry. Repairs that can be minimize this problems is periodic repair of the meatball molding machine, make SOP (Standard Operating Procedure), and make standard of raw materials production.